2022
DOI: 10.3389/fmicb.2022.919111
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive comparison of fecal microbiota in three ecological bird groups of raptors, waders, and waterfowl

Abstract: Gut microbiota plays a vital role in maintaining the health and immunity of wild birds. However, less is known about the comparison of fecal microbiota between different ecological groups of wild birds, particularly in the Yellow River National Wetland in Baotou, China, an important transit point for birds migrating all over the East Asia-Australian and Central Asian flyways. In this study, we characterized the fecal microbiota and potential microbial function in nine bird species of raptors, waders, and water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 74 publications
2
5
0
Order By: Relevance
“…Firmicutes was the dominant phylum (73% of total reads) in the falcon gut followed by Actinobacteria and Proteobacteria (Fig 4A). These observations are consistent with previous studies that have found falcon gut microbiomes to consist of Firmicutes, Proteobacteria and Actinobacteria [17][18][19][20][22][23][24]. All but one of the studies have small sample sizes (n = 1-11, S4 Table) [18][19][20][22][23][24].…”
Section: Salmonella Is Associated With the Falcon Gut Microbiota Func...supporting
confidence: 91%
See 1 more Smart Citation
“…Firmicutes was the dominant phylum (73% of total reads) in the falcon gut followed by Actinobacteria and Proteobacteria (Fig 4A). These observations are consistent with previous studies that have found falcon gut microbiomes to consist of Firmicutes, Proteobacteria and Actinobacteria [17][18][19][20][22][23][24]. All but one of the studies have small sample sizes (n = 1-11, S4 Table) [18][19][20][22][23][24].…”
Section: Salmonella Is Associated With the Falcon Gut Microbiota Func...supporting
confidence: 91%
“…Although recent studies have revealed flight, body size, and migration patterns are associated with the gut microbiota in birds [16] the effect of evolutionary histories and diet on the bird gut microbiota remains poorly characterized. Furthermore, studies investigating gut microbiomes of uber-carnivorous raptors whose diet almost exclusively consists of animal flesh, are underrepresented, with the exception of a few studies that include a small number of raptors [16][17][18][19][20][21][22][23][24]. Birds of the genus Falco (henceforth referred to as falcons) are unique among raptors as they are genetically distinct from other flesh-eating birds of prey such as hawks, eagles and vultures, all of which belong to a single taxonomic order-Accipitriformes [25].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding genera, the intestinal microbiota of black-necked cranes comprised 15 dominant bacterial genera and 18 dominant fungal genera. A higher percentage of these were Lactobacillus , Megamonas , and Enterococcus , which were widely distributed in other birds and were influential in regulating intestinal health, metabolic capacity, and antimicrobial activity ( Gao et al., 2021 ; Zhao et al., 2022 ). Remarkably, we also discovered several genera that are opportunistically pathogenic, including Pseudomonas , Pantoe , Escherichia , Burkholderia , Helicobacter , Fusarium , and Rhodotorula ( Xiang et al., 2019 ; Wang et al., 2020 ; Wu et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…We conducted an LEfSe analysis taking into account the different overwintering regions and found a few unique flora at the genus level, such as Enterococcus , Tausonia , and Botrytis in the LZ group; Lactobacillus , Naganishia , Mycosphaerella , Rhodotorula , Alternaria , and Sporisorium in the SN group; Clostridium, Fusarium, Debaryomyces, Cephalotrichum , and Arthrinium in the LS group; and Megamonas , Fusobacterium , Anaerobiospirillum , Campylobacter , Escherichia , Filobasidium , and Sporobolomyces in the RKZ group. Probiotics such as Enterococcus , Megamonas , Clostridium , and Lactobacillus have been proven in studies to enhance intestinal microenvironment, metabolic capacity, and antimicrobial activity ( Yang et al., 2012 ; Gao et al., 2021 ; Zhao et al., 2022 ). However, Fusarium and Rhodotorula may be harmful to cranes ( Wu et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation